Aberrant Splicing and Premature Termination of Transcription of the FVIII Gene as a Cause of Severe Canine Hemophilia A: Similarities with the Intron 22 Inversion Mutation in Human Hemophilia - Hough, Christine; Kamisue, Seiki; Cameron, Cherie; Notley, Colleen; Tinlin, Shawn; Giles, Alan; Lillicrap, David (Thrombosis and Haemostasis, 2002)
We have identified the causative mutation in the hemophilia A dog colony at Queen’s University, Canada and have observed a striking similarity with the intron 22 inversion found in ∼45% of severely affected hemophilia A patients. The canine hemophilia A phenotype arises from aberrant splicing and premature termination of transcription of the FVIII gene, resulting in a polyadenylated transcript lacking exons distal to 22 and terminating with a novel sequence element (NSE). In dogs and other species including humans, this NSE is present in low copy number. One copy of these sequences in the canine genome is within intron 22 and reveals differences in the hybridization banding patterns between normal and hemophilic DNA, suggestive of a large genomic rearrangement. The mutation mechanism may not be uncommon, as identical mutant transcripts were isolated from two hemophilia A littermates that are unrelated to the Queen’s colony and from hemophiliac dogs in the colony at Chapel Hill.
Keywords: Hemophilia; mutation; splicing